Image processing using a reconfigurable platform: Pre-processing block hardware architecture - Chiranjeevi G. N.; Subhash Kulkarni (International Journal of Reconfigurable and Embedded Systems (IJRES), 2021)
Real time image processing is a challenging task in which fetching the sub image requires offset memory access apart from core processing needs. This paper aims at overcoming the offset needs for memory addressing in pre-processing blocks. Another feature of this present work is to appending the image data with customized algorithmic reequipments viz duplicating, zero padding. For KxK kernel size, the proposed hardware architecture can be programmed to fetch K pixels in one cycle, reducing the data access time. Results have been compared with software-based processing for KxK spatial filtering. performance indicates significant timing improvement using proposed pre-processing hardware block.